Immunogenicity and safety of a trivalent inactivated influenza vaccine - Eddy Fadlyana; Kusnandi Rusmil; Novilia Sjafri Bachtiar; Rachmat Gunadi; Hadyana Sukandar (Indonesian Pediatric Society, 2011)
Background Trivalent inactivated influenza vaccines (TIV) containing antigens of two influenza A strains, A(H1N1) and A(H3N2), and one influenza B strain, are the standard onnulation for influenza prevention. The vaccines must be updated annually to provide optimal protection against the predicted prevalent strains for the next influenza season.Objective To assess the immunogenidty and safety of the inactivated influenza vaccine (Flubio®) in adolescents and adults, 28 days after a single dose.Methods In this experimental, randomized, single-blind, bridging study, we included 60 healthy adolescents and adults. A single, 0.5 mL dose was administered intramuscularly in the deltoid muscle of the left ann. Blood samples were obtained before and 28 days after immunization. Standardized hemagglutination inhibition (HI) test was used to assess antibody response to influenza antigens.Results From January to February 2010, a total of 60 adolescents and adults enrolled in the study, but two participants did not provide the required blood samples. One hundred percent of the subjects had an anti-influenza titer ≥ 1:40 HI units to all three strains, A/Brisbane/59/2007 (H1N1), A/Uruguay/716/2007 (H3N2), and B/Brisbane/60/2008 (P=1.000) after immunization. The Geometric Mean Titers (GMT) after immunization increasedfor all strains: A/Brisbane, 76.4 to 992.7, A/Uruguay, 27.6 to 432.1, and B/Brisbane, 19.9 to 312.7. Twenty eight days after immunization, we found a 4 times increase in antibody titers in 75.8% of the subjects for A/Brisbane, 84.5% for A/Uruguay, and 77.6% for B/Brisbane. We also observed that 100% of seronegative subjects converted to seropositive for all 3 strains. All vaccines were well-tolerated. There were no serious adverse events reported during the study.Conclusion In adolescents and adults, the Flubio® vaccine was immunogenic and safe.",